PERAN ELECTRONIC LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN - Waliyul Maulana Siregar; Fandi Setiawan; Ria Purwasih (Universitas Negeri Medan, 2022)
Abstract: The dynamics of people's lives are constantly evolving, changing and shifting. This is influenced by the development of science, technology and communication from time to time as well as the development of various interests that make people try to develop their potential. In the learning process the teacher can provide services without having to deal directly with students. The most recent thing is the development of what is called